Bank Management : A Decision-Making Perspective - Timothy W. Koch (Cengage Learning Asia, 2014)
Closely examine the impact of today's changing, competitive environment on commercial banks and banking services, as well as the entire financial services industry, with Koch/MacDonald's BANK MANAGEMENT, 7E. This new edition reflects the latest changes and developments, from complete regulatory updates to details of the many programs evolving amidst today's financial crises. The book's unique approach to understanding bank management focuses on decision-making in today's financial world. Whether you are a practicing or future professional, the book clearly demonstrates how certain factors influence credit, investment, funding, and pricing decisions. The book's solid framework provides an appreciation and understanding of the trade-offs between return and risk. You gain a better understanding of the most important issues confronting financial and banking managers today as the book discusses basic financial models used to formulate decisions and analyzes the strengths and weaknesses of data analysis. With the help of this latest edition, you develop the logical thought processes needed to achieve strong financial and management results.